Impact of digital transformation: assessing the knowledge and adoption of disruptive technologies in a higher education institution - Aquino, Janet; Alarcón, Roger; Guevara, Laurita; Bravo-Jaico, Jessie; Germán, Nilton; Valdivia-Salazar, Carlos; Serquén, Oscar; Maquen-Niño, Gisella Luisa Elena; Tesén-Arroyo, Alfonso (Frontiers in Computer Science, 2025)
Digital transformation has become a key factor for educational development since it not only involves the integration of disruptive technologies but also the restructuring of the process and cultural adaptation that allows Higher Education Institutions (HEI) to respond to changes in society and the demands of the labor market. This article aimed to determine the level of knowledge about the different aspects of digital transformation in a HEI, encourage the adoption of disruptive technologies and facilitate an effective transition to digital educational environments through an analysis based on 6 dimensions such as: important principles and definitions, technological support for DT, Digital tools, disruptive technologies in DT, Security in Information Technologies and Digital Culture, applying two surveys as instruments to teachers, students and graduates of the university community. A quantitative approach with quasi-experimental design was used, evaluating a pre-test and post-test with a total of 34 questions distributed among the six dimensions analyzed using a Likert scale and applying the Wilcoxon statistical test for related samples. The initial findings indicate that in the first dimension “important principles and definitions” with 6 questions, two of them do not present adequate significance with values of 0.06505 and 0.051, respectively. On the other hand, the dimensions technological support (6 questions), Disruptive technologies (9 questions), Digital tools (6 questions) and Information Technology Security (ICTs; 4 questions), obtained significant results in each of their questions, finally the Digital Culture dimension (4 questions) presents a question with a p-value of 0.24 presenting no significant difference, that is, the answers of the participants did not vary. In addition, at the dimension level, the one that shows the best results is Disruptive Technologies with a p-value of 9.08×10−17, which indicates that after the training, significant improvements were obtained in this dimension as opposed to the rest. Finally, performing the global analysis of the dimensions in terms of gender the scores in women are higher with respect to men, in addition, considering the analysis based on roles it was determined that teachers show better results and students have lower scores.